Mechanism of action of liver growth induced by peroxisome proliferators - Amer, Abeer H. A. (2011)
Humans are ubiquitously exposed to peroxisome proliferators including hypolipidemic agents, industrial solvents and atural products. Because of this and the fact that peroxisome proliferators cause non-genotoxic hepatocarcinogenesis in rodents, it is of importance to elucidate the mechanism of action of the peroxisome proliferators in order to provide an assessment of the hazard, if any, of these compounds to humans. It is also known that the peroxisome proliferators begin their actions by inducing hepatic DNA synthesis. Thus, the aim of this thesis was to find genes that could be responsible for triggering the induction of hepatic DNA synthesis caused by peroxisome proliferators, specifically ciprofibrate. First, it was important to indicate when the induction of hepatic DNA synthesis actually happens. This was done with BrdU immunohistochemical procedures. The induction of hepatic DNA synthesis with ciprofibrate in mice was observable only after 4 days making it difficult to specify when the induction actually happened. In rats the induction of hepatic DNA synthesis was found to peak at 24 hours and this system gave the better opportunity to find the genes responsible. The difference in the timing of induced hepatic DNA synthesis betweenmice and rats implied that there could be a species difference in the mechanism of each species’ response to PPAR. With immunohistochemistry it was noticed that there was a difference in the lobular localization of hepatic DNA synthesis in the liver tissues of rats and mice dosed with different inducers, with the rat livers exhibiting periportal distribution while hepatic DNA synthesis in the mice seemed to be distributed throughout the liver tissue. The effects of ciprofibrate or cyproterone acetate on liver gene expression in rats were studied, using cDNA microarrays, transcriptome sequencing and quantitative real- time PCR. A 1- 5 hour treatment period was chosen to detect the immediate early gene response, while a 24 hour time point was chosen to elucidate the confounding effects from the hepatic DNA synthesis seen during the 24 hour stimulation. The results showed that ciprofibrate altered the expression of numerous genes including previously known PPARa agonist-responsive genes involved in processes such as PPAR signalling pathways, fatty acid metabolic pathway, cell cycle, palmitoyl-CoA hydrolase activity, lipid metabolism, inflammatory responses, and stress responses, in addition to a large number of novel candidate genes. Three novel induced genes G0s2, Ccnd1 and Scd1, (and two marker genes CYP4A1 and CYP3A1) were confirmed with quantitative real- time PCR. The G0s2, Ccnd1 and Scd1 were found to be up-regulated at the hours 1 and 3 after dosing and not 24 hours, and the G0s2 and Scd1 were specific for the ciprofibrate suggesting they were involved in a distinct PPARa pathway responsible for the hepatic DNA synthesis. The complete database of the transcriptional response provided here opens doors of opportunity for further research to identify genes responsible for the liver growth induced by peroxisome proliferators.